The Rhetoric of the Norwegian Constitution Day: A Topos Analysis of Young Norwegian Students' May 17 Speeches, 2011 and 2012. Issue 2 (3rd March 2016) - Tønnesson, Johan Laurits; Sivesind, Kirsten
Abstract : National Day, or Constitution Day, in Norway, May 17, is often referred to as Children's Day. On this day, thousands of young Norwegian students march in parades and participate in celebrations in schoolyards and similar meeting places. Some students are selected to give speeches, performed in front of family members, neighbors, classmates, and most often teachers and the school principal. We analyzed 30 speech manuscripts, 12 from 2011 and 18 from 2012, and examined how the Constitution is expressed by a selection of topoi. The present study is the first one to examine how students engage in the constitution by giving speeches. Thus, our paper provides new insights into contemporary conceptions about the Constitution, as well as how students act in terms of school, society, and democracy.